Loss of factor VIII in zebrafish rebalances antithrombin deficiency but has a limited bleeding diathesis - Azhwar Raghunath; Catherine E. Richter; Megan S. Griffin; Sylvia M. Emly; Murat Yaman; Valder R. Arruda; Benjamin J. Samelson-Jones; Jordan A. Shavit (Blood Advances)
Abstract: Deficiencies in coagulation factor VIII (FVIII, F8) result in the bleeding disorder hemophilia A. An emerging novel therapeutic strategy for bleeding disorders is to enhance hemostasis by limiting natural anticoagulants, such as antithrombin (AT3). To study pro/anticoagulant hemostatic balance in an in vivo model, we used genome editing to create null alleles for f8 and von Willebrand factor (vwf) in zebrafish, a model organism with a high degree of homology to the mammalian hemostatic system and unique attributes, including external development and optical transparency. f8 homozygous mutant larvae surprisingly formed normal thrombi when subjected to laser-mediated endothelial injury, had no overt signs of hemorrhage, although they did have a modest increase in mortality. We have previously shown that at3–/– larvae develop disseminated intravascular coagulation (DIC), with spontaneous thrombosis and fibrinogen consumption, resulting in a bleeding phenotype marked by secondary lack of induced thrombus formation upon endothelial injury. We found that with loss of FVIII (f8–/–;at3–/–), larvae no longer developed spontaneous fibrin thrombi and produced clots in response to endothelial injury. In contrast, homozygous loss of zebrafish Vwf failed to rescue the at3 DIC phenotype. These findings demonstrate an altered balance of natural anticoagulants that mitigates FVIII deficiency in zebrafish, similar to hemostatic drugs in the clinical development pipeline, and suggest that zebrafish FVIII might circulate independently of Vwf. Further exploration of this unique balance in zebrafish could provide novel insights into the treatment of hemophilia A and von Willebrand disease.